THE EFFECT OF BRAND IMAGE AND QUALITY PERCEPTIONS ON TRUST AND THEIR IMPACT ON THE DECISION TO BUY HAND SANITIZER - Nathanael Priltius; Wahono Sumaryono; Sri Widyastuti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Along with the increasing activity of people, especially in urban areas, and thenumber of instant products that are fast-paced and practical, an innovativewaterless hand sanitizer product has emerged, known as antiseptic hand sanitizeror hand sanitizer. This hand sanitizer product contains an antiseptic used to killgerms on hands, which consists of alcohol and triclosan. Based on data from2015 - 2020 which is the result of a Top Brand survey of hand sanitizer users inIndonesia, it is found that the Antis and Dettol brand hand sanitizers always havean index that places them in the top two positions in that period. In this study, twoindependent variables were selected including brand image and perceivedquality, with the assumption that the independent variables were proven to havea positive relationship with trust and purchasing decisions. This research wasconducted in five areas of DKI Jakarta (West Jakarta, East Jakarta, CentralJakarta, North Jakarta, and South Jakarta) in November - December 2020. Thesample used was 200 respondents. The data analysis technique used StructuralEquation Model (SEM), in this case, Liserel. The results of the study concluded:1) Brand Image affects consumer confidence in antis products; 2) Quality affectsconsumer confidence in antis products; 3) Brand Image affects consumerdecisions to buy antis products; 4) Quality influences consumer decisions to buyantis products; 5) Trust affects consumer decisions to buy antis products; 6)Brand image and quality can explain 86% of the trust variance, while theremaining 14% is explained by other factors. Brand image, quality, and trust canexplain 92% of the variance of purchasing decisions while the remaining 8% isexplained by other factors; and, 7)There are direct and indirect effects of brandimage and quality variables on the decision to buy antis products. The indirecteffect is through the variable of consumer confidence in antis products.